Bioenergetic insufficiencies due to metabolic alterations regulated by PD-1 are an early driver of CD8(+) T cell exhaustion - Bengsch, Bertram (Immunity, 2016)
Dynamic reprogramming of metabolism is essential for T cell effector function and memory formation. However, the regulation of metabolism in exhausted CD8(+) T (Tex) cells is poorly understood. We found that during the first week of chronic lymphocytic choriomeningitis virus (LCMV) infection, before severe dysfunction develops, virus-specific CD8(+) T cells were already unable to match the bioenergetics of effector T cells generated during acute infection. Suppression of T cell bioenergetics involved restricted glucose uptake and use, despite persisting mechanistic target of rapamycin (mTOR) signaling and up-regulation of many anabolic pathways. PD-1 regulated early glycolytic and mitochondrial alterations and repressed transcriptional coactivator PGC-1α. Improving bioenergetics by overexpression of PGC-1α enhanced function in developing Tex cells. Therapeutic reinvigoration by anti-PD-L1 reprogrammed metabolism in a subset of Tex cells. These data highlight a key metabolic control event early in exhaustion and suggest that manipulating glycolytic and mitochondrial metabolism may enhance checkpoint blockade outcomes.